Strategy for Local Plant-Based Material Valorisation to Higher-Value Feed Stock for Piglets - Sarunas Badaras; Modestas Ruzauskas; Romas Gruzauskas; Egle Zokaityte; Vytaute Starkute; Ernestas Mockus; Jolita Klementaviciute; Vadims Bartkevics; Laurynas Vadopalas; Dovile Klupsaite; Agila Dauksiene; Gintare Zokaityte; et al. (Animals, 2022)
In this study, a 41-day experiment was conducted using 300 (21-day-old) Large White/Norwegian Landrace piglets (100 piglets in each group). Three dietary treatments were compared: (i) a basal diet (C-I), (ii) a basal diet with the addition of extruded–fermented wheat bran (Wex130/screwspeed25Lpa) (TG-II), and (iii) a basal diet with the addition of dried sugar beet pulp (TG-III). Analyses of piglets’ blood parameters, faecal microbial and physico-chemical characteristics, and piglets’ growth performance were performed. It was found that the extrusion and fermentation combination led to an additional functional value of Wex130/screwspeed25Lpa, which showed desirable antimicrobial and antifungal properties in vitro (inhibited 5 out of 10 tested pathogenic strains and 3 out of 11 tested fungi). Both treatments reduced total enterobacteria and increased lactic acid bacteria counts in piglets’ faeces. The consistency of the piglets’ faeces (in all three groups) was within a physiological range throughout the whole experiment. Strong positive correlations were found between the LAB count in piglets’ faeces and butanoic acid; butanoic acid, 3-methyl-; butyric acid (2-methyl-); pentanoic acid. The treatment groups obtained a significantly higher body weight gain and average daily gain. Finally, substituting the piglets’ diet with Wex130/screwspeed25Lpa and sugar beet pulp led to favourable changes in micro-organism populations in the piglets’ faeces as well as better growth performance.